Iliac crest and femoral bone marrow as the source of plastic-adherent cells (Medical Journal of Indonesia, 2011)
Background: Many studies have used iliac crest as the source of mesenchymal stem cells. In cases of long bone shaft fracture, obtaining marrow from the fracture site offers more advantages. Nevertheless, due to the high number of fat cells in long bones, the yellow marrow of long bones is believed to contain lower number of mesenchymal stem cells than red marrow. Therefore the aim of this study is to compare the potency between red and yellow marrow as the donor site for the isolation of mesenchymal stem cell. Methods: Bone marrow of eight giant Flemish rabbits was aspirated from the iliac crest and femoral shaft. Mononuclear cells were isolated from both aspirates and expanded in low glucose DMEM. After eight weeks, the cells were harvested and counted using improved Neubauer hemocytometer. Comparison of the cell number between the two donor sites was then performed by t-test. Results: After 8 weeks, an average number of 2.93 ± 0.91 x 104 and 3.7 ± 2.50 x 104 cells were obtained from the iliac and femoral group respectively. No statistically significant difference was found between those two groups (p = 0.45). Conclusion: Plastic-adherent cells can be isolated and expanded from both iliac crest and femoral shaft.